INTERRELATION OF YIELD AND ITS COMPONENTS IN COTTON (Gossypium hirsutum L.) GENOTYPES - SAJID, MA; JATOI, WA; KALERI, AA; MANZOOR, D; ULLAH, N; AFZAL, A; SHAHZADI, I; AHMED, M; AHMED, F; ASGHAR, S (Biological and Clinical Sciences Research Journal, 2024)
Cotton is regarded as a profitable crop that gives people fiber and shelter. Research focuses on how yield, its components, and related attributes work together to enhance cotton. During the Kharif season of 2022, the present study was completed, implementing a randomized complete block design with ten genotypes and three replications. The study took place at the Nuclear Institute of Agriculture (NIA), located in Tandojam. This work aimed to examine the correlation and regression between upland cotton genotypes and heritability estimates for traits associated with yield. The outcomes showed that all of the parameters in the mean square of the ANOVA were significant. In contrast to the remaining genotypes, genotype FH-142 displayed the most favorable performance; it had the tallest plants, more sympodial branches, more bolls per plant, an improved seed index, and the longest staple length. The genotype CRIS-342 came in second, exhibiting good plant height, sympodial branches, a good number of bolls per plant, a ginning outturn, and the highest boll weight among the other genotypes. The findings of the correlation and regression indicated that the number of bolls per plant-1 had a highly significant and positive relationship with monopodial branches plant-1 (r = 0.73*) and (b = 2.45) and that the number of bolls per plant had a strong relationship with seed cotton yield plant-1 (r = 0.83**) and (b = 3.29). Staple length and seed cotton yield plant-1 had a negative correlation (-0.77*) with regression (b = -4.58). The highest heritability estimates in the broad sense are for monopodial branch plants (84.61), ginning outturn% (97.03), bolls plant-1 (93.96), plant height (90.70), staple length (79.31), and seed index (71.42). However, the boll’s weight showed a low heritability (23.71). Further breeding programs can utilize genotype FH-142 to increase the number of sympodial branches, increase the number of boll plants, and improve the staple length. Genotype CRIS-342 can be utilized for medium-stature plant height, boll weight, and better ginning outturn. However, genotype NIA-BT-40 can be utilized for short-strategy plants with the highest ginning output.